Redressing the balance: Commentary on "Examining motor learning in older adults using analogy instruction" by Tse, Wong, and Masters (2017). (September 2018) - Bobrownicki, Ray; Collins, Dave; Sproule, John; MacPherson, Alan C.
Abstract: Tse, Wong, and Masters (2017) recently published a study that indicated that analogy instruction may help older adults acquire resilient motor skills that require reduced cognitive processing compared to traditional explicit instruction. Although we do not dispute that analogy learning may prove useful for this population, in this commentary, we contend that there are methodological issues in this research—which are shared with previous studies comparing analogy and explicit instruction—that potentially limit ecological validity, impact the size of detected effects, influence the development and understanding of associated theory, and, as such, constrain resulting recommendations for applied practice. Of particular concern is the comparison of the single -item analogy instruction to the list of nine explicit instructions, which risks conflating the effects of the type of instruction with the volume of instruction. We further argue that the benefits of analogy may be more parsimoniously explained by the instruction's capability to succinctly convey skill (rather than its potential for limiting reinvestment), but that this capability may only be realised if the to-be-learned analogy is relevant and readily understood by the learner. Finally, we suggest that research in this area must look to incorporate more rigorous methods that compare experimental conditions to representative reference groups that allow us to explore how and when to deploy the myriad instructional tools available to practitioners and learners.